2018
DOI: 10.1186/s12936-018-2305-6
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up malaria intervention “packages” in Senegal: using cost effectiveness data for improving allocative efficiency and programmatic decision-making

Abstract: BackgroundSenegal’s National Malaria Control Programme (NMCP) implements control interventions in the form of targeted packages: (1) scale-up for impact (SUFI), which includes bed nets, intermittent preventive treatment in pregnancy, rapid diagnostic tests, and artemisinin combination therapy; (2) SUFI + reactive case investigation (focal test and treat); (3) SUFI + indoor residual spraying (IRS); (4) SUFI + seasonal malaria chemoprophylaxis (SMC); and, (5) SUFI + SMC + IRS. This study estimates the cost effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…Nonetheless, the overall results presented here are in line with a recent study in Senegal which similarly found reductions in incidence greatest in areas that received both IRS and SMC (52% reduction) compared to areas that received IRS (38% reduction) or SMC (32% reduction) alone [27] and recent modeling studies that indicate a high probability of strong synergies between complementary IRS and population-based drug interventions such as mass drug administration [25,26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nonetheless, the overall results presented here are in line with a recent study in Senegal which similarly found reductions in incidence greatest in areas that received both IRS and SMC (52% reduction) compared to areas that received IRS (38% reduction) or SMC (32% reduction) alone [27] and recent modeling studies that indicate a high probability of strong synergies between complementary IRS and population-based drug interventions such as mass drug administration [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…Developing this evidence base is a challenge, however, as the most robust methods for generating evidence (e.g., cluster randomized trials) are often unrealistic-the time, resources, and expertise required, and limited space available, are prohibitive. Observational/ecological studies can help address these challenges by allowing the geographical and temporal linking of malaria intervention coverage data, ecological and environmental data, and data from routine surveillance activities in order to provide insight into how trends in malaria incidence change in response to various interventions or packages of interventions [11,27]. Observational research questions are also adaptable to the unique malaria control landscape that exists in each country, taking advantage of 'natural experiments' that result from programme implementations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the predicted health benefits are comparable with current estimates of other interventions, such as the DALYS averted by the use of HIV protease inhibitors to prevent recurrent malaria incidence in HIV infected children [5,6] and prevention campaigns [54]. With respect to intervention costs, although higher costs per person unsurprisingly reduced the number of countries where a severe malaria intervention is cost-effective, our estimates of the ICER are comparable to various scale-up programs [55], and the effects of media on promoting life-saving practices [56].…”
Section: Discussionsupporting
confidence: 57%
“…In addition, the predicted health benefits are comparable with current estimates of other interventions, such as the DALYS averted by the use of HIV protease inhibitors to prevent recurrent malaria incidence in HIV infected children [5,6] and prevention campaigns [42]. With respect to intervention costs, although higher costs per person unsurprisingly reduced the number of countries where a severe malaria intervention is cost-effective, our estimates of the ICER are comparable to various scale-up programs [43], and the effects of media on promoting life-saving practices [44].…”
Section: Discussionsupporting
confidence: 57%